RESEARCH ALGORITHM FOR BUSINESS ENTERPRISE ORGANIZATIONAL SUSTAINABILITY INDICES - A. V. Kouznetsov (Модернизация, инновация, развитие)
Abstract. It is recommended that organizational sustainability of a business enterprise be assessed on the basis of a system of indices brought down in the article to characterize to what extent an option of the company organizational structure contributes to gaining higher final activity results. The indices may be used as efficiency criteria for options of the company organizational structure and management system. It is reasonable to assess each index from the viewpoint of its impact on the business company organizational and economic sustainability and to try either to eliminate the negative impact or to strengthen the positive role with respect of this sustainability.